Pengaruh Paparan Medan Magnet Extremely Low Frequency (ELF) dalam Proses Fermentasi Tape - Zakiya El Firdausi; Sudarti .; Yushardi . (CV. ITTC INDONESIA, 2023)
Extremely low frequency magnetic field or ELF is included in electromagnetic waves with frequencies smaller than 300 Hz. The use of ELF with a certain frequency intensity and time can be utilized for various fields, one of which is in the tape fermentation process. Exposure to very low frequency magnetic fields (ELF) with a certain frequency intensity and exposure time will have a different impact on the tape produced. The impact of ELF exposure with a frequency intensity of 300 μT and 500 μT and a certain time produces different microbes, pH values, and textures. In finding the relationship between ELF exposure with microbes, pH value, and texture, research was conducted using the article review method, using 20 journals published around 2015-2023. Collecting data that can be strengthened and facts about exposure to very low frequency magnetic fields (ELF) that play a role in maintaining pH so that it can help the tape fermentation process. The results obtained are the longer the exposure time and the greater the intensity of the ELF frequency given, the more it will suppress the microbial proliferation rate, the greater the frequency intensity and the longer the exposure time of the extremely low frequency (ELF) frequency tends to stabilize the acidity value of the tape, and the smaller the pH value of the tape, the more sour the taste of the tape tends to be bitter with a strong alcohol aroma and a softer tape texture.